Pulmonary Artery Stent Implantation for Fibrosing Mediastinitis: Our Clinical Experience - Cheng Hong; Daibing Zhou; Haiming Chen; Xiaofeng Wu; Wenliang Guo; Jiangyu Cui; Weijie Guan; Nanshan Zhong; Jielong Lin (Pulmonary Circulation, 2025)
ABSTRACT Fibrosing mediastinitis (FM) can block pulmonary vessels and airways, hindering treatment efficacy. Pulmonary artery (PA) stenting might provide a solution in such cases. This study involved 30 patients who had 49 PA stenting procedures for FM. Data on baseline characteristics, CT pulmonary angiography images, stent patency, and hemodynamics were collected. Patients with FM often had a history of chronic obstructive pulmonary disease (15/30), tuberculosis (12/30), and pneumoconiosis (11/30). Patients exhibited typical symptoms such as dyspnea, exercise intolerance, and cough. FM appeared as multiple bilateral shadows with enlarged hilar and mediastinal lymph nodes. Our study found that the PA involvement alone was predominantly in the left and right lower basilar trunk, with the left lower pulmonary arteries (LLPA) involved in 80% of cases and the right lower pulmonary arteries (RLPA) in 100%. Moreover, over 2/3 of patients showed involvement of both PA and pulmonary vein (PV), mainly in the bilateral upper lung lobes, then in the right middle lobe and left lingual lobe. After PA stent implantation, patients showed enhanced tricuspid annular plane systolic excursion (20.6 vs. 18.5, p < 0.001) and reduced right atrial diameter (35.5 vs. 37.3, p = 0.042), along with significant gains in 6‐min walk distance (465.2 vs. 392.7, p = 0.002) and improved World Health Organization functional class (p < 0.001). Hemodynamic parameters improved after PA stent placement with significant reductions in systolic pulmonary artery pressure (PAP) (51.1 vs. 64.2, p < 0.001), mean PAP (28.4 vs. 35.2, p < 0.001), pulmonary vascular resistance (4.7 vs. 5.9, p = 0.004), and stent gradient (11.2 vs. 33.4, p < 0.001), along with increased patency (84.8% vs. 28%, p < 0.001), and fractional flow reserve (0.84 vs. 0.44, p < 0.001). Over a median follow‐up of 331 days (range 45–980), no significant stent stenosis occurred (p = 0.287). Mild adverse events like cough and mild hemoptysis were noted during the procedure. Secondary intervention was needed for 5 of 49 stents. PA stents placement, especially the LLPA and RLPA, improved pulmonary vascular patency, hemodynamics, and symptoms.